Sixteen Weeks of Concurrent Training Do Not Increase the Magnitude of the Post-Exercise Hypotensive Effect in Hypercholesterolemic Morbid Obesity Patients; [Sedici Settimane Di Allenamento Concomitante Non Aumentano L’Entità Dell’Effetto Ipotensivo Post-Esercizio in Pazienti Ipercolesterolemici Con Obesità Patologica] - Herrera-Valenzuela, T (Edizioni Minerva Medica, 2024)
BACKGROUND: It is widely known that concurrent exercise of moderate-intensity continuous plus resistance training (CTMICT+RT) decreases blood pressure in hypertensive and multiple patients with other comorbidities such as obesity, however, there is little information about the changes in the ‘magnitude’ of the post-exercise hypotension effect (PEH) observed from an ‘acute’ to after long-term ‘chronic’ exercise adaptations. To determine both acute and chronic effects of 16 weeks of exercise using CTMICT+RT in the magnitude of the systolic (SBP)/diastolic (DBP) blood pressure response of hypercholesterolemic patients with morbid obesity. Secondarily, to determine the CTMICT+RT effects on fasting plasma glucose, lipid profile and body composition. METHODS: A quasi-experimental study was designed where morbid obesity patients were assigned to normal cholesterol (Ncho, N.=19) and the hypercholesterolemia (Hcho, N.=13) groups according to their total cholesterol levels. The main outcomes were SBP/DBP blood pressure, and secondary outcomes; fasting plasma glucose, lipid profile outcomes, and body composition (body fat, lean mass, skeletal muscle mass) variables. RESULTS: Training-induced effects analyses revealed that 16 weeks of CTMICT+RT promoted significant chronic reductions in SBP in the Hcho group from pre- to post-10 min (135 vs. 119 mmHg, P=0.004). There were significant reductions in the Ncho group in Tc (188.0 vs. 117.4 mg/dL, P=0.050), and similarly, in triglycerides from before to after the CTMICT+RT intervention (188.0 vs. 117.4 mg/dL, P=0.050). The magnitude of the PEH detected in SBP in the Hcho group (-6 mmHg) was not observed and decreased post-16 weeks of CTMICT+RT (-4 mmHg, P=0.535). CONCLUSIONS: Sixteen weeks of CTMICT+RT promote acute and chronic SBP decreases in hypercholesterolemic morbid obesity patients, being the acute ‘magnitude’ of SBP/DBP response not increased after CTMICT+RT COPYRIGHT © 2024 EDIZIONI MINERVA MEDICA.